Defensive mechanisms and personality structure in an early adolescent boy: process and outcome issues in a non-intensive psychoanalytically oriented psychotherapy - Daniela Di Riso; Alessandro Gennaro; Silvia Salcuni (Research in Psychotherapy, 2015)
The main aim of this paper is to empirically assess defense mechanisms trends and personality structure in a once a week psychoanalytically oriented psychotherapy with an early adolescent, affected by a General Anxiety Disorder (GAD). Assessment and outcome measure included the Shedler-Westen Assessment Procedure for Adolescents (SWAP-200-A); process was evaluated through defensive mechanisms analysis, using Defense Mechanisms Rating Scale (DMRS). The paper focused on 12 sessions divided into three periods, along 2 years of treatment. Quantitative and narrative profiles of SWAP-200-A and DMRS were integrated; a log linear procedure was chosen to assess defensive mechanisms trends longitudinally during the treatment. Moreover a Multiple Correspondence Analysis (MCA) was applied to DMRS to provide a map of the evolution of the patterns of defense mechanisms throughout the course of treatment. Personality assessment and defensive mechanisms showed an inhibited self-critical image with obsessive, narcissistic and disavowal patterns. According to trends during treatment phases, MCA analysis identified decreasing in defensive patterns, while mature defenses increased significantly. The study highlighted how non-intensive psychoanalytic psychotherapy can help early adolescents with clinical problems to improve their overall mental functioning. Outcome in terms of personality structural changes and process according to defense mechanisms were discussed to highlight improvement not just in symptomatology, but also in personality structure and functioning.